PENERAPAN METODE MULTI SENSORI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 009 AIR EMAS - Edi Supadmi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the lack of writing skills of students. This is due to: (a) instructional methods used by teachers always lectures, discussion and provision of duty; (b) students are not trained to write well and truly in the study; (c) the student is only assigned to write his own without the guidance of a teacher; and (d) interaction in the learning occurs only in one direction. To that end, researchers conducted research is conducted with the aim of improving students' writing skills by applying multi-sensory methods in classroom action research. This study was conducted in two cycles, data collection techniques used were observation activities of teachers and students, and a written test. Results of the study stated that through multi-sensory method of increasing students' writing ability. This is evidenced by: (a) the activities of teachers has increased in the first cycle to the second cycle. In the first cycle in the implementation of learning first meeting with a percentage of 45% after the second meeting with a percentage of 55%. Cycle II increased in all three meetings with the percentage of 70% and after the fourth meeting accomplished 75%. Besides the student activity also increased in the first cycle of the first meeting keatifan students reached 48% and in the second meeting reached 61%. In the second cycle to the 3rd meeting with the percentage of 71% and 4 meeting to reach 84%; and (b) the students' writing skills also increased in the first cycle in the implementation of learning first meeting with a percentage of 45% after the second meeting with a percentage of 55%. Cycle II increases at a meeting to 3 with a percentage of 70% and after the fourth meeting accomplished 75%.